Perceptions of public secondary head teachers in science in Region I of their supervisory role - Cruz, Natividad Arcelona
To determine the perceptions of Region I secondary school head teachers in science of their supervisory role in the public high schools is the purpose of the study. It specifically sought to determine the nature and extent of the supervisory tasks of the secondary head teachers, their overall attitude towards the performance of their tasks, their actual performance and their perception of the extent of their effectiveness in their tasks. The study also surveyed perceptions on the qualifications of secondary school head teacher in science that contribute to their effectivity and the problems they perceive in relation to their tasks.